Process design and scale up for Al recovery from saline slags and zeolite production - David Blanco; Alejandro Jiménez; Antonio Gil; Miguel Angel Vicente; Mariano Martín (Process Safety and Environmental Protection, 2026)

Performance assessment of no-fee GNSS augmentation systems for tractor guidance - Jaime Gomez-Gil; Angel Alonso-Garcia; Sergio Alonso-Garcia; Fco. Javier Gomez-Gil (Computers and Electronics in Agriculture, 2026)

Strategic assessment of socio-environmental conflicts in solar hydrogen production: a case of Antofagasta, Chile - Isidora Abasolo Farfan; Alejandro Fernández Gil; René Garrido Lazo; Carolina Bonacic Castro; Pablo Rodríguez Machuca; Daniel Serafini; Roberto Carmona Campos; Angel Rodríguez Soto; Marcelo Mena-Carrasco Soto; Luis Ramirez Camargo; Javier Valdes; Yunesky Masip Macia (Clean Technologies and Environmental Policy, 2026)

Morpho-phylogenetic characterization and pathogenicity of emerging fungi causing dieback and stem blight of blueberry in Sinaloa, Mexico - Perla R. Nuñez-Garcia; Angel Rebollar-Alviter; Raymundo S. García-Estrada; Kamila C. Correia; Guillermo Marquez-Licona; Joaquín G. Ramírez-Gil; Guadalupe A. Mora-Romero; Juan M. Tovar-Pedraza (Physiological and Molecular Plant Pathology, 2026)

Alternative biological functions of lactose: a narrative review - Augusto Anguita-Ruiz; Hassan Vatanparast; Corinna Walsh; Giovanni Barbara; Sharon Natoli; Bronwyn Eisenhauer; Jaime Ramirez-Mayans; G. Harvey Anderson; Mathilde Guerville; Amandine Ligneul; Angel Gil (Critical Reviews in Food Science and Nutrition, 2025)

Glycogen Synthase Kinase-3β Inhibitor VP3.15 Ameliorates Neurogenesis, Neuronal Loss and Cognitive Impairment in a Model of Germinal Matrix-intraventricular Hemorrhage of the Preterm Newborn - Isabel Atienza-Navarro; Angel del Marco; Pilar Alves-Martinez; Maria de los Angeles Garcia-Perez; Alvaro Raya-Marin; Isabel Benavente-Fernandez; Carmen Gil; Ana Martinez; Simon Lubian-Lopez; Monica Garcia-Alloza (Translational Stroke Research, 2025)
Advances in neonatology have significantly reduced mortality rates due to prematurity. However, complications of prematurity have barely changed in recent decades. Germinal matrix-intraventricular hemorrhage (GM-IVH) is one of the most severe complications of prematurity, and these children are prone to suffer short- and long-term sequelae, including cerebral palsy, cognitive and motor impairments, or neuropsychiatric disorders. Nevertheless, GM-IVH has no successful treatment. VP3.15 is a small, heterocyclic molecule of the 5-imino-1,2,4-thiadiazole family with a dual action as a phosphodiesterase 7 and glycogen synthase kinase-3β (GSK-3β) inhibitor. VP3.15 reduces neuroinflammation and neuronal loss in other neurodegenerative disorders and might ameliorate complications associated with GM-IVH. We administered VP3.15 to a mouse model of GM-IVH. VP3.15 reduces the presence of hemorrhages and microglia in the short (P14) and long (P110) term. It ameliorates brain atrophy and ventricle enlargement while limiting tau hyperphosphorylation and neuronal and myelin basic protein loss. VP3.15 also improves proliferation and neurogenesis as well as cognition after the insult. Interestingly, plasma gelsolin levels, a feasible biomarker of brain damage, improved after VP3.15 treatment. Altogether, our data support the beneficial effects of VP3.15 in GM-IVH by ameliorating brain neuroinflammatory, vascular and white matter damage, ultimately improving cognitive impairment associated with GM-IVH.

Multifunctional nanocomposites based on kaolinite/titania/iron applied to hydrogen peroxide production and bisphenol–A removal - Marcus Vinicius do Prado; Vinicius Lima; Larissa Oliveira; Eduardo J. Nassar; Liziane Marçal; Emerson Henrique de Faria; Miguel Angel Vicente; Raquel Trujillano; Leticia Santamaría; Antonio Gil; Sophia Korili; Katia Jorge Ciuffi (Applied Clay Science, 2024)

Single cell ICP-MS to evaluate the interaction behaviour for Cd, Ce and U with Streptomyces coelicolor spores - Steffen Hellmann; Paula García-Cancela; Sergio Alonso-Fernández; Mario Corte-Rodríguez; Jörg Bettmer; Angel Manteca; Dirk Merten; Teba Gil-Díaz; Thorsten Schäfer; María Montes-Bayón (Chemosphere, 2024)

Evaluation of mechanical, physical and chemical properties of ecological modular soil-alkali activated bricks without Portland cement - Lucas Félix da Costa Gonçalves; Carlos Eduardo Tino Balestra; Miguel Angel Ramirez Gil (Environmental Development, 2023)

Effect of concentration of biosynthesized zinc oxide nanoparticles on the growth and development of Lycopersicon esculentum - David Asmat-Campos; Eloy López-Medina; Efraín Gil-Rivero; Luigi Villena-Zapata; Angel Carreño-Ortega (Biocatalysis and Agricultural Biotechnology, 2023)

Kitul, a food plant with antidiabetic-like effects: Reduction of intracellular reactive species in glucose-stimulated RIN-5F pancreatic β-cells and mitigation of pro-inflammatory mediators in activated RAW 264.7 macrophages - Catarina Andrade; David M. Pereira; Nelson G. M. Gomes; Federico Ferreres; Angel Gil-Izquierdo; Paula B. Andrade; Sutsawat Duangsrisai; Patrícia Valentão (Food Research International, 2023)

Contribution to low-carbon cement studies: Effects of silica fume, fly ash, sugarcane bagasse ash and acai stone ash incorporation in quaternary blended limestone-calcined clay cement concretes - Carlos Eduardo Tino Balestra; Lilyanne Rocha Garcez; Leandro Couto da Silva; Márcia Teresinha Veit; Eliziane Jubanski; Alberto Yoshihiro Nakano; Marina Helena Pietrobelli; Ricardo Schneider; Miguel Angel Ramirez Gil (Environmental Development, 2023)

Categorization and Analysis of Relevant Factors for Optimal Locations in Onshore and Offshore Wind Power Plants: A Taxonomic Review - Isabel C. Gil-García; M. Socorro García-Cascales; Ana Fernández-Guillamón; Angel Molina-García (Journal of Marine Science and Engineering, 2019)
Wind power is widely considered to be a qualified renewable, clean, ecological and inexhaustible resource that is becoming a leader in the current energy transition process. It is a mature technology solution that was quickly developed and has been massively integrated into power systems in recent years. Indeed, a remarkable number of renewable integration policies have been promoted by different governments and countries. With the aim of maximizing the power given by wind resources, the locations of both onshore and offshore wind power plants must be optimized following a sort of different criteria. Under this scenario, a number of factors and decision criteria in the evaluation and selection of locations can be identified. Moreover, the relevant wind power increasing in the power generation mix is addressed, along with a standardization of factors and decision criteria in the optimization and selection of such optimal locations. In this context, this paper describes a systematic review and meta-analysis combining most of the contributions and studies proposed during the last decade. Thus, our aim is focused on reviewing and categorizing all factors to be considered for optimal location estimation, pointing out the differences among the selected factors and the decision criteria for onshore and offshore wind power plants. In addition, our review also includes an analysis of the representative key indicators for the contributions, such as the annual frequency of publications, geographical classification, analysis by category, evaluation method and determining factors.

Impact of climate change on solar irradiation and variability over the Iberian Peninsula using regional climate models - Victoria Gil; Miguel Angel Gaertner; Claudia Gutierrez; Teresa Losada (International Journal of Climatology, 2019)
As solar energy will be an increasingly important renewable energy source in future years, the study of how climate change affects both its temporal and spatial variability is very relevant. In this paper, we study future changes of the solar radiation resource in the Iberian Peninsula (IP) through a set of simulations from ESCENA project (generation of regionalized scenarios of climate change in Spain with high‐resolution models) until mid‐century. The evaluation of the simulations against observations indicates contrasting biases for the different regional climate models (RCMs) in terms of solar irradiation amount and its inter‐annual variability. We propose a diagnostic for the quality of solar energy resource, in which the gridpoints are classified in four categories depending on the combination of solar irradiation amount and variability. The observed large percentage of points in the optimal category (high irradiation/low variability) in the IP is well‐captured by the RCMs in general terms. The analysis of scenarios indicates a future increase in solar irradiation, although not all scenarios agree in the geographical distribution of this increase. The quality of solar energy resource is projected to increase, mostly due to a decrease in variability. This is an important result, as a more stable inter‐annual resource should decrease the need for backup sources and also reduce inter‐annual electricity price variations. Finally, results from a first approximation to the issue of the ability of solar energy to cover power demand peaks in summer show important differences between regions of the IP. However, the spatially averaged correlation of solar irradiation and summer surface temperatures for the whole IP is rather high, which is a positive result as the strong interconnections of the power grid within the IP could allow a distribution of solar power surpluses in certain regions for such high‐temperature episodes.

Modification of appetite by bread consumption: A systematic review of randomized controlled trials - Carolina Gonzalez-Anton; Reyes Artacho; Maria D. Ruiz-Lopez; Angel Gil; Maria D. Mesa (Critical Reviews in Food Science and Nutrition, 2017)

Novel kinematic indices for quantifying upper limb ability and dexterity after cervical spinal cord injury - Ana de los Reyes-Guzmán; Iris Dimbwadyo-Terrer; Soraya Pérez-Nombela; Félix Monasterio-Huelin; Diego Torricelli; José Luis Pons; Angel Gil-Agudo (Medical & Biological Engineering & Computing, 2017)

Impacts of climate change on biodiversity in Israel: an expert assessment approach - Marcelo Sternberg; Ofri Gabay; Dror Angel; Orit Barneah; Sarig Gafny; Avital Gasith; José M. Grünzweig; Yaron Hershkovitz; Alvaro Israel; Dana Milstein; Gil Rilov; Yosef Steinberger; et al. (Regional Environmental Change, 2015)

Betalains in the era of global agri-food science, technology and nutritional health - Diego A. Moreno; Cristina García-Viguera; José I. Gil; Angel Gil-Izquierdo (Phytochemistry Reviews, 2008)

Bioavailability of phenolic acids - Sophie Lafay; Angel Gil-Izquierdo (Phytochemistry Reviews, 2008)

Engineering pancreatic islets - Bernat Soria; Etel Andreu; Genoveva Berná; Esther Fuentes; Amparo Gil; Trinidad León-Quinto; Franz Martín; Eduard Montanya; Angel Nadal; Juan A. Reig; Cristina Ripoll; Enrique Roche; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

Decalcification by ascorbic acid for immuno- and affinohistochemical techniques on the inner ear - Angel Merchán-Pérez; P. Gil-Loyzaga; Maria Visitación Bartolomé; Manuel Remezal; Pilar Fernández; Teresa Rodríguez (Histochemistry and Cell Biology, 1999)